Numerical Solution for Hybrid Fuzzy Differential Equation by Fifth Order Runge-Kutta Nystrom Method - Jayakumar Thippan; Muthukumar Thangamuthu (Journal of Mathematical Sciences and Modelling, 2019)
This  study  discusses a numerical methods for hybrid fuzzy differential equations by fifth order RK Nystrom Method for fuzzy differential equations. We prove the convergence result and give numerical examples to illustrate the theory.